2021
DOI: 10.37637/ab.v4i3.744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Metode Seleksi Populasi F3 Tanaman Kedelai Berdasarkan Heritabilitas dan Kemajuan Seleksi

Abstract: Dalam upaya mendapatkan varietas unggul dibutuhkan metode seleksi yang tepat. Penelitian ini bertujuan untuk mendapatkan metode seleksi yang sesuai pada populasi F3. Penelitian dilaksanakan mulai Oktober sampai Desember 2020 di desa Raya Usang Kecamatan Dolok Masagal, kabupaten Simalungun. Penelitian menggunakan Rancangan Augmented. Setiap individu tanaman ditanam dalam baris sesuai metode seleksi (single seed descent, bulk dan pedigree). Tetua ditanam sebanyak tiga ulangan. Jarak tanam yang digunakan 20 x 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Traits controlled by additive gene action will have a high response to selection as the traits of interest and can be helpful as selection criteria for further improvement (Varona et al, 2018). Previous studies reported that pure line selection and mass selection were beneficial for traits managed by an additive gene action in the foxtail millet (Prasanna et al, 2013), while Meriaty et al (2021) used pedigree selection for such traits in soybean. Non-additive gene action governed the inheritance of three targeted traits in the foxtail millet breeding program, i.e., plant height, heading time, and grain weight per plant.…”
Section: Resultsmentioning
confidence: 99%
“…Traits controlled by additive gene action will have a high response to selection as the traits of interest and can be helpful as selection criteria for further improvement (Varona et al, 2018). Previous studies reported that pure line selection and mass selection were beneficial for traits managed by an additive gene action in the foxtail millet (Prasanna et al, 2013), while Meriaty et al (2021) used pedigree selection for such traits in soybean. Non-additive gene action governed the inheritance of three targeted traits in the foxtail millet breeding program, i.e., plant height, heading time, and grain weight per plant.…”
Section: Resultsmentioning
confidence: 99%
“…In many plants, seed characters are used to select the best genotypes to breed. According to Meriaty et al (2021), the number of pods characterizes a rather high genetic advancement, suggesting that there is a good chance that these traits will be passed down to the following generation and that selecting soybean genotypes with numerous pods is quite simple.…”
Section: Evaluation Of Variability Heritability and Selection Of 2 Nd...mentioning
confidence: 99%
“…Pedigree selection is based on individual performances from the best families (Arifiana and Sjamsijah, 2017). This selection can be started in the early generations and is generally always recorded during the selection process, so the lineage is known in detail (Meriaty et al, 2021). This selection method also can be used for gaining a high yield sorghum variety.…”
Section: Evaluation Of Variability Heritability and Selection Of 2 Nd...mentioning
confidence: 99%